El diseño de la agenda política y la construcción de alternativas de solución en la política de inmigración española (2007)
The aim of this article is to analyze a public policy - the immigration policy in Spain in the last twodecades- using the multiple-streams framework, developed by John Kingdon. Following this approach,in order to explain the public policy, two processes will be mainly explored: the agenda setting processand the process of specification of alternatives from which a choice is to be made; along with the political processes associated with these changes.